Putative 3D Structure of QcrB from Mycobacterium tuberculosis Cytochrome bc1 Complex, a Novel Drug‐Target for New Series of Antituberculosis Agent Q203. (22nd April 2016) - Ko, Yoonae; Choi, Inhee
Abstract : Tuberculosis caused by Mycobacterium tuberculosis is still a serious world health problem. There is an urgent need for an effective drug against rapidly arising multiple‐drug resistant M. tuberculosis (MDR‐TB) and extensively drug resistant M. tuberculosis (XDR‐TB) strains. Q203 was recently reported as the most promising M. tuberculosis agent, which is also active against MDR‐TB and XDR‐TB. The cytochrome b subunit of the cytochrome bc 1 complex (QcrB) was identified as a drug target in M. tuberculosis (Rv2196) for Q203. Herein, we have built the homology models of M. tuberculosis QcrB WT and T313A mutants using the X‐ray structures of other species' QcrB as templates: Rhodobacter sphaeroides, Paracoccus denitrificans, yeast and bovine. The model with the best quality based on the structural validation results was selected for docking and used for analyzing Q203‐binding mode. These insightful information will be beneficial to the further development of imidazo pyridine amide series as novel antituberculosis drugs. Abstract :